1977
DOI: 10.1111/j.1469-8986.1977.tb01142.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of State‐Trait Anxiety on the Ability to Enhance and Suppress EEG Alpha

Abstract: The purpose of this study was to explore the relationship between self‐reported state and trait anxiety and the ability to enhance or suppress (i.e., control) alpha density in a biofeedback situation. Forty subjects were randomly divided into alpha enhancement and alpha suppression conditions and then underwent four 40‐min eyes‐closed biofeedback sessions. Immediately before and after each session, each subject completed the A‐State scale of the State‐Trait Anxiety Inventory (STAI). Prior to the first session … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1977
1977
2009
2009

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…For instance, the most common measures reported are amplitude, as measured in microvolts, and measures based on a ratio of the amount of EEG activity seen when at rest. However, reward thresholds based on amplitude have ranged from 10 mV up to 218 JOURNAL OF NEUROTHERAPY 40 mV (e.g., Ancoli & Green, 1977;Hardt & Kamiya, 1976a;Holmes et al, 1980;Kuhlman & Klieger, 1975;Nowlis & Kamiya, 1970;Valle & DeGood, 1977) with some setting additional upper limits of 75 mV and 100 mV (Marshall & Bentler, 1976;Tyson, 1982). There is a similar level of variety when using thresholds based on a proportion of resting EEG activity, with thresholds set at between 50% and 85% of the amount of alpha seen when at rest (e.g., Cho et al, 2008;Cram, Kohlenberg, & Singer, 1977;Norris et al, 2001;Prewett & Adams, 1976;Travis et al, 1974Travis et al, , 1975.…”
Section: Reward Thresholdmentioning
confidence: 99%
“…For instance, the most common measures reported are amplitude, as measured in microvolts, and measures based on a ratio of the amount of EEG activity seen when at rest. However, reward thresholds based on amplitude have ranged from 10 mV up to 218 JOURNAL OF NEUROTHERAPY 40 mV (e.g., Ancoli & Green, 1977;Hardt & Kamiya, 1976a;Holmes et al, 1980;Kuhlman & Klieger, 1975;Nowlis & Kamiya, 1970;Valle & DeGood, 1977) with some setting additional upper limits of 75 mV and 100 mV (Marshall & Bentler, 1976;Tyson, 1982). There is a similar level of variety when using thresholds based on a proportion of resting EEG activity, with thresholds set at between 50% and 85% of the amount of alpha seen when at rest (e.g., Cho et al, 2008;Cram, Kohlenberg, & Singer, 1977;Norris et al, 2001;Prewett & Adams, 1976;Travis et al, 1974Travis et al, , 1975.…”
Section: Reward Thresholdmentioning
confidence: 99%
“…These subjects exhibit strong activation of EEG under basal conditions and increase in α-activity upon sensory stimulation [5,6]. A relationship was revealed between high psychological reactivity, range of effective frequencies of photostimulation provoking an entrainment reaction, and degree of this reaction [5].…”
Section: Resultsmentioning
confidence: 93%
“…These findings suggest that the biofeedback-induced enhancement of alpha and theta provide additional benefits to the presumed placebo effects of suppression. Three studies (Valle & DeGood, 1977;Plotkin & Rice, 1981;Rice et al, 1993) showed that clinical improvement could be obtained without increased alpha, proving that there is a placebo effect in neurotherapy. This is not surprising, because all successful therapy is known to have a placebo effect.…”
Section: Discussionmentioning
confidence: 97%
“…Unlike clinical practice, the training period was brief, which may explain the poor outcome. Valle and DeGood (1977) trained 20 students in alpha (8.5-13.5 Hz) enhancement, and an equal number in alpha suppression. Audio feedback occured when alpha exceeded 10 µV.…”
Section: Generalized Anxiety Disordermentioning
confidence: 99%